Hybrid Energy Storage Power Allocation Strategy Based on NGO-VMD - Haiyan WANG; Linyu QIAN (Zhongguo dianli)
Power fluctuations during wind power grid connection affect the stability of the power grid. To address this issue, a hybrid energy storage power allocation strategy based on the northern goshawk optimization (NGO) algorithm was proposed to optimize the parameters of variational mode decomposition (VMD). Firstly, the generation power of wind power was filtered in accordance with the regulations of wind power grid connection technology using the adaptive averaging filtering method, and the fluctuation power was calculated from the filtered power. Then, the optimal combination of K value (number of decomposition modes) and α value (quadratic penalty factor) in the NGO-VMD algorithm was used to realize power allocation between lithium batteries and supercapacitors after the fluctuation power signal was decomposed by VMD. Finally, the state of charge (SOC) of the hybrid energy storage system (HESS) was optimized using dual fuzzy control to achieve the secondary power allocation of the HESS. Simulation outcomes demonstrate that employing this control strategy achieves not only compliance with the maximum power fluctuation requirements of wind power grid connection but also the maintenance of SOC within a reasonable range, ensuring the long-term secure operation of HESS.